Migration Intelligence: AI and Bio-surveillance of Migration Flows- - Giacomo Buoncompagni (Journal of Digital Information Management, 2021)
The Coronavirus pandemic has made the use of artificial intelligence even more pervasive. States have decided to initiate bio-surveillance, through automated drones and other types of technologies such as GPS in mobile phones, to track COVID-19 positive individuals through apps or smart thermal cameras to control the spread of the virus. The current health crisis is making us deal with the dilemma regarding ‘invisible populations’, and migrants in particular, which involves a number of social and technological problems. On the one hand, lack of visibility is a systematic aspect of population management that can benefit both governments and the people concerned. The illusion of a ‘data panoptic’ does not take into account the conditions under which data are collected, the gaps or limitations of an interoperable system: in any system, not everything is counted, and not in the same way. This invisibility can come in handy for shadowy economies and unscrupulous politicians ready to sound Security alarms. On the flip side, for categories such as the homeless, prisoners, migrants and sex workers, invisibility can be a defence against attention that too often resembles control and surveillance. The technodigital management of migratory flows and migrants’ data clashes with ethical-legal issues that are still open, and which concern all those sectors that involve the massive use of technology. Issues that in this case have become the two big questions of the current research: does data monitoring risk becoming a control mechanism that hinders the recognition of fundamental human rights? Is it currently possible to predict the real risks and harms of the technologies used to digitally manage migration? The central thesis presented in this article aims to high as a result of neural network training actions) can significantly influence the management of migration flows in the (post)pandemic society. The methodology adopted is based on an in-depth study of legal, socio-political and technological academic literature and a comparison of different sources. It examines current trends in the development of digital tools and the consequences these may have for international migration and the individual lives of migrants in the host country. It is believed that this reflection, although mainly theoretical, can contribute to the debate on the future of digital management of international migration, inviting policy makers and experts in this field to reflect on the complexity of the relationship between AI and migrants, in order to develop an open, secure, ethical and shared data system as soon as possible. Furthermore, a new concept, called ‘Migration Intelligence’ will be introduced, and it is understood here as a set of specific activities concerning identity checks, border security and management, and analysis of biometric data on migrants, refugees and asylum seekers. and the consequences these may have for international migration and the individual lives of migrants in the host country. It is believed that this reflection, although mainly theoretical, can contribute to the debate on the future of digital management of international migration, inviting policy makers and experts in this field to reflect on the complexity of the relationship between AI and migrants, in order to develop an open, secure, ethical and shared data system as soon as possible. Furthermore, a new concept, called ‘Migration Intelligence’ will be introduced, and it is understood here as a set of specific activities concerning identity checks, border security and management, and analysis of biometric data on migrants, refugees and asylum seekers.

Machine Learning in Predicting the Appropriate Model of Software Process Models Deviation- - Tarik Chaghrouchni; Issam Mohammed Kabbaj; Zohra Bakkoury (Journal of Digital Information Management, 2018)
Software Process Model deviation management allows to supervise process model execution and its adaptation when an inconsisteny is detected. The process model should be adjusted based on specified rules in order to ensure the continuity of  the process model execution. Journal of Digital Information Management “priority and dependency of sub-activities “ and data from previous executions to predict the appropriate software process model. Subject Categories and Descriptors D.2.3 [Software Coding Tools and Techniques]; F.1.1 Models of Computation Some works attempted to handle process model deviation by adjusting fragments and considering some rules to ensure that all constraints are met. Other studies considered only critical constraints in order to avoid cost/ schedule overrun: rules considering the criticality of the activities and their order. However, it is still generating uncertain executions with no mastery on the final result

Machine Learning in Predicting the Appropriate Model of Software Process Models Deviation - Tarik Chaghrouchni; Issam Mohammed Kabbaj; Zohra Bakkoury (Journal of Digital Information Management, 2018)

Major Issues in Adoption of Electronic Health Records- - Myongho Yi (Journal of Digital Information Management, 2018)
The use of Electronic Health Records (EHRs) is not new, but the implementation and provision of their services are. Despite the positive aspects and promising features of EHRs use in medical and healthcare practices, there are many issues that need to be identified and addressed to expedite the adoption rate of EHRs. The objective of the study is to examine major issues which hinder EHR adoption and to present identified solutions.

Major Issues in Adoption of Electronic Health Records - Myongho Yi (Journal of Digital Information Management, 2018)

Mashup Service Implementation on Multi-cloud Environment Using Map Reduction Approach - Venkateswara Rao Peddada; Ali Hussain Mohd (Journal of Data Processing, 2018)

Mathematical Formulation for Programmers to Select Background and Foreground Colors in Designing Websites - Veeresh Duvvuri; Srinivas Laggoni; Shankar Karinga (International Journal of Web Applications, 2018)

MCWDF - Micro-chunk based Web Delivery Framework - Shailesh Shivakumar; P.V Suresh (Progress in Computing Applications, 2018)

Measuring Software Architecture Stability Evolution in Object-oriented Open Source Systems - Hassan Almousa; Mamdouh Alenezi (Journal of Information Technology Review, 2018)

Mining of Social Networks from Classic Books and Visualization - Seung Jin Lim (Journal of Digital Information Management, 2018)

Mining of Social Networks from Classic Books and Visualization- - SeungJin Lim (Journal of Digital Information Management, 2018)
While modern online social networks offer unprecedented amount of data and opportunities for mining, we acknowledge that other forms of social networks have been around throughout human history. In particular, we recognize the classic books as valuable sources for the analysis of interpersonal interactions as they have had positive influence on human mind and continue to enlighten the human race.

A Mixed Chaotic-cellular Automata Based Encryption Scheme for Compressed Jpeg Images - Rabab Beniani; Kamel Mohamed FARAOUN (Journal of Multimedia Processing and Technologies, 2018)

Model Integration Approach from SysML to MATLAB/Simulink- - Bassim CHABIBI; Adil ANWAR; Mahmoud NASSAR (Journal of Digital Information Management, 2018)

Model Integration Approach from SysML to MATLAB/Simulink- - Bassim CHABIBI; Adil ANWAR; Mahmoud NASSAR (Journal of Digital Information Management, 2018)
In system engineering process, descriptive system models seem to be insufficient in order to perform a system verification which fulfils various stakeholders’ requirements. This aspect is well handled by simulation process through the use of several simulation techniques or algorithms. As a consequence, design process efficiency is considerably reduced by the fact that both system modeling and simulation tools are often used separately. This study introduces an integration process to unify the potential provided by systems modeling languages and simulation environments, through the definition of a Domain Specific Language, namely Simulation Modeling Language, that is built on the basis ofa deep study of common constructs, semantics and modeling methodologies of several simulation environments, in addition to the specification of a model transformation between this language and a simulation environment (MATLAB/SImulink) in order to illustrate both its importance et its efficiency in our integration approach. Through the specification of its syntaxes and semantics, the defined intermediate modeling language allows modeling systems by using common constructs and modeling methodologies of simulation process in order to ensure their modeling with simulation environments

Model of “International Megalesson” of Learning Programming in Schools of Russia and Kazakhstan - Zhamilya Akkassynova; Nikolay Pak; Liubov Ivkina (Progress in Computing Applications, 2018)

A MultiCriteria Spatial WEB Decision Support System for Hazardous Materials Road Transport - Djamila Hamdadou; Emdjed Alnafie; Karim Bouamrane; Ikram Behilil (Transactions on Machine Design, 2018)

Multicast optimization and node fast location search method for wireless sensor networks based on ant colony algorithm - Wang, R.; He, G.; Wu, X.; Wang, F.; Hu, Y. (Journal of Digital Information Management, 2017)

Multicast Optimization and Node Fast Location Search Method for Wireless Sensor Networks Based on Ant Colony Algorithm- - Ruiying Wang, Guoping He; Xiaoming Wu; Fuqiang Wang; Yifan Hu (Journal of Digital Information Management, 2017)
Wireless sensor network is a new information acquisition and processing technology. A large number of sensor nodes form a network through self-organization including each node integrates sensing unit, processing unit, communication unit and energy supply. The protocol multicast technology of wireless sensor network routing is a means of group communication, which requires information from the source node at the same time sent to multiple destination nodes, routing as the core technology of multimedia networks, its scope of study is extensive, including routing protocols, routing strategy and routing algorithms. In this paper, we mainly study the multicast routing algorithm which is based on Quality of Service (QoS), and introduce the search strategy which is based on the shortest path of pheromone in the process of ant colony feeding. MATLAB ant colony algorithm is also used in the WSN routing protocol multicast problem in the application of the problem solving for local optimization. The result of computer simulation shows that the ant colony algorithm has a better effect on solving the multicast protocol of WSN, and the algorithm can realize the fast positioning and query of wireless sensor network routing nodes.

Model of e-commerce cloud warehouse grading based on mass simulation data - Wang, F.; Wang, Y.-L.; Liu, Z.-J.; Cui, X.; Zhang, P. (Journal of Digital Information Management, 2016)

Modeling the evolution of collaboration network and knowledge network and their effects on knowledge flow through social network analysis - Zhang, Y.-R.; Ma, D. (Journal of Digital Information Management, 2016)

A malicious peers detection framework for peer-to-peer systems - Wei, X.; Fan, J.; Wang, T.; Wang, Q. (Journal of Digital Information Management, 2015)

Medical image retrieval based on an improved non-negative matrix factorization algorithm - Wang, J.; Lai, S.Y.; Li, M.D.; Lies, D.H. (Journal of Digital Information Management, 2015)

Mining Frequent patterns through microaggregation in differential privacy - Ni, Z.; Li, Q.M.; Liu, X.Q.; Li, T.; Hou, R. (Journal of Digital Information Management, 2015)

Model Computing System for Emergent Infectious Disease Prevention and Control Ability Evaluation of Medical Building Network - Zhang, H.; Zhang, S.; Liu, N. (Journal of Digital Information Management, 2015)

Modeling and simulation of DIGSILENT-based micro-grid system - Zhang, Y.; Zhu, X.; Li, Q.; Liu, T. (Journal of Digital Information Management, 2013)
The accurate modeling of micro-grid access to power system planning and design stage needs is the primary problem to solve. This paper modeled the micro grid photovoltaic power generation system, including silicon solar cell, photovoltaic inverters, battery energy storage system, and the micro power distribution system. In the use of power system analysis software (DIGSILENT) of actual power system simulation, the simulation results verify the model's correctness. In the power grid fault disturbance, the light intensity of disturbance and the load disturbances, the simulation results show that the optical storage combined with micro network has fast dynamic response characteristics, and its network of grid-connected voltage influenced by the changes of the light and load is little, while more affected by the network fault influence.
Keywords: Battery energy storage system; Micro grid; Photovoltaic inverter; Silicon solar cell

The modeling of genetic and Tabu search algorithm based BP neural network in the risk analysis of investment - Yang, L.; Yunlong, D. (Journal of Digital Information Management, 2013)
There are many parameters which affect the economic benefit indicators for evaluation and they are all uncertain. Because of the parameters' uncertainty, evaluation indicators values of economic benefit in project investment are also uncertain. In these years, more and more BP Neural network based models are established to evaluate the risk of investment for its characters of wide information distribution and strong fault tolerance. However, the internal defect of local minima problem in this model will greatly discount the effects of evaluation if the training data are not proposed selected. To solve this problem of traditional BP neural network, an optimization algorithm that combines the advantages of genetic algorithm (GA) and Tabu Search (TS) is proposed. The training process is divided into two phases in order to search promising parameters of the BP neural network in favor of better evaluation and analysis of the investment. In the first phase, the initial parameters are first searched by GA algorithm by taking advantage of its various searches of the solutions, and the best parameters are selected by Tabu search algorithm in the second phases. After calculation of practical data, it proves that the new algorithm has better convergence rate and predictive accuracy, which make the evaluation and risk analysis of the investment faster and more accurate.
Keywords: BP Neural Network; Genetic Algorithm; Investment Evaluation; Risk Analysis; Tabu Search Algorithm

Modeling resource-constrained project scheduling problem and its solution by genetic algorithm - Chai, C. (Journal of Digital Information Management, 2013)
The optimization of the resource-constrained project scheduling is an NP-hard problem. Complexity of the algorithm for solving this problem increases exponentially with the increase of resource constraints. Therefore, traditional optimization methods based on Excel tables cannot calculate the efficient allocation of resources, which will affect the scheduling of project management resources. The optimization problem like multiple resource-constrained project scheduling demands an optimization method based on genetic algorithm, which adopts the decimal encoding based on activity priority combined with the storage of the adjacency matrix in order to effectively solve unauthorized phenomenon in activity scheduling. It also adopts preemption mode of allocation of resources in activities to avoid conflict in resource allocation. Besides, we designs C language program that realizes heuristic genetic algorithm, which can find out the most excellent duration that meets the resource constraints through multiple iterations. Finally, the practical results indicate that genetic algorithm can quickly and efficiently solve this problem.
Keywords: Genetic Algorithm; NP-hard problem; Project scheduling; Resource constraints

Mechanism analysis of protocols based on the FPCPN model - Wang, W. (Journal of Digital Information Management, 2012)
Focusing on the protection of privacy and non- publicity of special networks, the CPN model is extended to PCPN by the protocol factor and the formal model. The FPCPN (Formal Protocol Colored Petri Net) is presented to analyze the operation mechanism of protocols. It is introduced by four steps, such as the whole structure, the network element conversion, the conditions of transition triggers/executions and sub-system partitions. Finally, the feasibility and efficiency of FPCPN is validated by an example.
Keywords: CPN; FPCPN; Mechanism of protocol; Petrinet

Middleware model for adapting dynamic requirements - Suganthi, S.; Nadarajan, R. (Journal of Digital Information Management, 2012)
Making a distributed system adaptable to the dynamic variations in the user requirements is a big challenge in software industries. It is identified that the solution for the adaptability of such dynamic variations can be achieved through reflective middleware. In this paper an efficient solution is proposed by combining aspect oriented approach with reflective middleware. The significant feature of the proposed aspect oriented reflective middleware model is capturing the dynamic variations in the functionalities of the system as aspects. The three major components defined in this model to implement dynamic adaptability are Aspect Generator, Aspect Weaver and Remote Method Invoker. Aspect Generator component is used to define dynamic requirements as aspects. Aspect Weaver provides service to weave the dynamic requirements with the application components associated with that requirement. Remote Method Invoker is the meta layer component, which provides the platform for the Aspect Weaver to execute its service. The metric to measure the efficiency of the system adaptability has also been proposed here. The adaptability approach implemented through this model has been evaluated and proved as an efficient solution using this metric. This model has also been evaluated at an architectural level using formal analysis to prove that the dynamic requirements can be incorporated without affecting the existing functionalities of the system.
Keywords: Adaptability Metric; Aspect-Oriented Approach; Aspect-Oriented Reflective Middleware; Dynamic Adaptation; Dynamic Requirements; Reflective Middleware

Modeling push-based live P2P streaming by stochastic activity networks - Zhang, P.; Helvik, B.E. (Journal of Digital Information Management, 2012)
Live P2P streaming has been widely used in recent years because of its scalability and low costs. At the same time, it meets some new challenges that centralized systems never faced, for example, churn and content pollution. It is the first paper which uses stochastic activity networks (SANs) to model and analyze pushbased live P2P streaming systems from the users' point of view. The model provides a new line of thinking to model push-based live P2P streaming, which enables the effect of churn, pollution and buffer size to be studied simultaneously. It explains why there is a gap between theoretical results in previous studies of content pollution in P2P streaming and the observed effect. It also points out the threshold of buffer size for non-significant QoS improvement.
Keywords: Modeling; P2P streaming; Pollution; QoS; Stochastic activity networks(SAN)

Mining the blogosphere to generate cuisine hotspot maps - Shih, C.-C.; Peng, T.-C.; Lai, W.-S. (Journal of Digital Information Management, 2010)
Choosing a restaurant is one of the most frequent decisions faced in modern daily life; however, it is difficult for consumers to choose between food/restaurant by reading large amounts of reviews. This study attempts to generate cuisine hotspot maps through blog content mining to help consumers make restaurant decisions by specialties. The main obstacle in doing this involves recognizing and extracting restaurants and essentialrestaurant information (i.e., restaurant dishes) in unstructured content. In contrast to traditional Named Entity Recognition (NER) targets, dish name is a promising target that received little attention in previous studies. This study develops methods for recognizing and extracting restaurant names and dish names from review postsin the blogosphere and achieves satisfactory performance. Based on the method, we processed more than 12,000 Chinese blog posts and generated a cuisine hotspot map. The map shows the most popular dishes of restaurants in a map-view to help consumers make restaurant decisions. A prototype of cuisine hotspot map, named CuisineGuide, is implemented and available as an iPhone application.
Keywords: Blog analysis; Hotspots; Name entity recognition; Web content; Web search

A MPEG-based architecture for generic distributed multimedia scenarios - Carreras, A.; Tous, R.; Rodríguez, E.; Delgado, J.; Cordara, G.; Francini, G.; Gibellino, D. (Journal of Digital Information Management, 2010)
This paper presents a standards-based architecture for a complex and generic distributed multimedia scenario, which combines content search and retrieval, DRM, and context-based content adaptation together. It is an innovative and totally generic approach trying to narrow the semantic-gap by integrating a fl exible language for multimedia search based on MPEG Query Format (MPQF) standard with the application of video analysis algorithms for the automatic extraction of low level features and with the use of contextual information.
Keywords: Context-based adaptation; Digital Rights Management-Rights Expression Language; Features extraction; MPEG query format

Multi-objective optimization in service systems - Gonsalves, T.; Yamagishi, K.; Itoh, K. (Journal of Digital Information Management, 2010)
Muti-objective optimization deals with the simultaneous optimization of two or more conficting objective functions in real-life systems. This paper deals with the multi-objective optimization in service systems. The goal of service systems is to provide cost-efficient service to customers, while at the same time, reducing the customer waiting time for service. In general, a low cost in system operation leads to longer waiting times, while a higher cost in system operation leads to shorter waiting times. The two objectives - service cost (operational cost) and waiting time (customer satisfaction) are, therefore, conficting in nature. We use the novel Multi-Objective Particle Swarm Optimization (MOPSO) algorithm to optimize the two conficting objective functions simultaneously. MOPSO is a fairly recent swarm intelligence meta-heuristic algorithm known for its simplicity in programming and its rapid convergence. The multi-objective optimization procedure is illustrated with the example of a practical service system. MOPSO produces a family of well-spread Pareto fronts for the two objective functions in the practical service system.
Keywords: Multi-Objective Particle Swarm Optimization; Service cost; Service systems; Simulation optimization

Machine learning based work task classification - Granitzer, M.; Rath, A.S.; Kröll, M.; Seifert, C.; Ipsmiller, D.; Devaurs, D.; Weber, N.; Lindstaedt, S. (Journal of Digital Information Management, 2009)
Increasing the productivity of a knowledge worker via intelligent applications requires the identification of a user's current work task, i.e. the current work context a user resides in. In this work we present and evaluate machine learning based work task detection methods. By viewing a work task as sequence of digital interaction patterns of mouse clicks and key strokes, we present (i) a methodology for recording those user interactions and (ii) an in-depth analysis of supervised classification models for classifying work tasks in two different scenarios: a task centric scenario and a user centric scenario. We analyze different supervised classification models, feature types and feature selection methods on a laboratory as well as a real world data set. Results show satisfiable accuracy and high user acceptance by using relatively simple types of features.
Keywords: Data model; Data structure; Work task classification user interaction

Maximizing mobile multimedia adhoc networks lifetime using a distributed cooperation mechanism - Bahi, J.M.; Eskandar, M.; Mostefaoui, A. (Journal of Digital Information Management, 2009)
Energy conservation is a critical issue in wireless mul tihop ad-hoc networks, which have nodes powered by batteries only. One major metric for energy conservation is that all nodes participate in relaying requests which may be opposite to its interest but can be a solution for extending the network lifetime. We proposed a distributed algorithm which gurabtuees a cooperation between the nodes in func tion of their energy provision. We focus in this paper on the exploitation of nodes mobility. Experiments results show the impact of nodes mobility on the behavior of our proposed algorithm.
Keywords: Distributed algorithm; Mobile ad hoc network; Nodes mobility

Mobile lab clients for testing application specific integrated circuits in education - Auer, M.E.; Zutin, D.G. (Journal of Digital Information Management, 2009)
The aim of this work is to develop a simultaneous multi user access system - READ (Remote ASIC Design and Test) that allows users to perform test and measurements remotely via clients running on mobile devices as well as on PCs. The system also facilitates the remote design of circuits with the PAC - Designer The system is controlled by LabVIEW and was implemented using a Data Acquisition Card from National instruments. Such systems are specially suited for manufacturing process monitoring and control. The performance of the simultaneous access was tested under load with a variable number of users. The server implements a queue that processes user's commands upon request.
Keywords: ASICs; Mobile devices; Mobile labs; Online laboratories; Remote systems; Server-client communication

Map integrity constraint verification by using visual language parsing - Del Fatto, V.; Deufemia, V.; Paolino, L. (Journal of Digital Information Management, 2008)
In the last decade there has been an increasing interest in the use of tools for the creation of geographic maps. However, these tools include functionalities that allow users to insert information without verifying their consistency with the constraints defined by the designer. In this paper we propose an approach based on visual language parsing for guaranteeing the integrity of data produced during the map editing process. According to our approach, constraints are expressed by using high-level data model, such as OMT-G, and converted in a proper visual language grammar automatically. From such a grammar, a parser able to identify incorrect aggregation of spatial data input is generated. The grammar formalism also allows us to associate suitable semantic actions with productions in order to perform automatic corrections of inconsistent input data, error recognition and visualization, prompting actions for error recovery. We also present a system prototype supporting the proposed process.
Keywords: Data Quality; Grammar Formalism; Integrity Constraint Checking; Spatial Consistency; Topologicalrelationships; Visual Language Parsing

Map integrity constraint verification by using visual language parsing - Fatto, V.D.; Deufemia, V.; Paolino, L. (Journal of Digital Information Management, 2008)
In the last decade there has been an increasing interest in the use of tools for the creation of geographic maps. However, these tools include functionalities that allow users to insert information without verifying their consistency with the constraints defined by the designer. In this paper we propose an approach based on visual language parsing for guaranteeing the integrity of data produced during the map editing process. According to our approach, constraints are expressed by using high-level data model, such as OMT-G, and converted in a proper visual language grammar automatically. From such a grammar, a parser able to identify incorrect aggregation of spatial data input is generated. The grammar formalism also allows us to associate suitable semantic actions with productions in order to perform automatic corrections of inconsistent input data, error recognition and visualization, prompting actions for error recovery. We also present a system prototype supporting the proposed process.
Keywords: Data Quality; Grammar Formalism; Integrity Constraint Checking; Spatial Consistency; Topological Relationships; Visual Language Parsing

Map-based interfaces for information management in large text collections - Mayer, R.; Roiger, A.; Rauber, A. (Journal of Digital Information Management, 2008)
The Self-Organising Map (SOM) has been proposed as an alternative interface for exploring Digital Libraries or other big document collections, in addition to conventional search and browsing. With advanced visualisations assisting the user in understanding the contents of the map and its structure, as well as advanced interaction modes as zooming, panning and area selection, the SOM becomes a feasible alternative to classical search interfaces. Several applications show the SOM's utility for this task. However, there are still shortcomings in helping the user understanding the ma, which is essential to fully exploit the SOM's potential as an Information Management tool. There are insufficient methods developed for describing the map to support the user in the analysis of the map contents. In this paper, we give an overview of existing techniques and applications of SOMs in Digital Libraries, and present recent work in assisting the user in exploring the map by automatically describing maps using advanced labelling and summarisation of map regions, focusing on text collections. Therewith, the SOM becomes an attractive tool for Information Management in large corpora.
Keywords: Map interfaces; Text collection

Model-driven development of content-based image retrieval systems - Ignatova, T.; Heuer, A. (Journal of Digital Information Management, 2008)
Generic systems for content-based image retrieval (CBIR), such as QBIC [7] cannot be used to solve domain-specific image retrieval problems, as for example, the identification of manuscript writers based on the visual characteristics of their handwriting. Domain-specific CBIR systems currently have to be implemented bottom up, i.e. almost from scratch, each time a new domain-specific solution is sought. Inspired by the recognition, that CBIR systems, although developed for different domain-problems, comprise similar-building blocks and architecture, the idea of adopting model-driven development techniques for generating CBIR systems was elaborated. To support the design of domain-specific CBIR-Systems on a conceptual level by reusing data structure and functional interfaces a framework model is developed, which can be used to derive concrete domain-specific CBIR models. A transformation approach for the generation of a platform-specific implementation on top of an object-relational database from the concrete conceptual model is proposed. Finally, how these techniques can be applied for the design of a CBIR system for the identification of music manuscript writers based on the visual characteristics of their handwriting is demonstrated.
Keywords: Content-based image retrieval; Model-driven development

Multiple description coding of an audio stream by optimum recovery transforms - Ito, A.; Makino, S. (Journal of Digital Information Management, 2008)
In this paper, we discuss a method of splitting one audio stream into two equal-quality streams and recover the original audio stream from only one of the split streams. From a mathematical consideration, it is found that the sum of errors of two recovered signals is equal to the power of the original signal if simple recovery is carried out. Next, we describe the optimum recovery transform. This method utilizes the covariance matrix of the signal to minimize the error of the recovered signal. We carried out several experiments to recover a signal from one of the split signals. The result showed that the optimum recovery transform gave better results than the simple recovery, while the best splitting transform differed according to the signal to be processed.
Keywords: Audio coding; Audio signal; Multiple description coding; Optimum recovery transform

A method of reduction of the microinstructions of synchronous digital systems - Al-Dahleh, M.Z.; Shehabat, I.M. (Journal of Digital Information Management, 2007)
In this paper, the author presents a method to synthesize the Algorithm State Machines (ASM) for synchronous digital systems using Combined Addressing. In This proposed method, the microinstructions are divided into subsets, and thus the Numbers of microinstructions are apparently minimized and the throughput time of the automation is reduced.
Keywords: Combined addressing; Digital systems; Microinstruction (MI); Synchronized systems; Throughput

A multilingual query processing system using software agents - Idicula, S.M.; David Peter, S. (Journal of Digital Information Management, 2007)
The goal of this work was developing a query processing system using software agents. Open Agent Architecture framework is used for system development. The system supports queries in both Hindi and Malayalam; two prominent regional languages of India. Natural language processing techniques are used for meaning extraction from the plain quety and information from database is given back to the user in his native language. The system architecture is designed in a structured way that it can be adapted to other regional languages of India. This system can be effectively used in application areas like e-governance, agriculture, rural health, education, nabonal resource planning, disaster management, information kiosks etc where people from all walks of life are involved.
Keywords: Database design; Interfaces; Query processing; Software agents

Multimedia knowledge representation for automatic annotation of broadcast TV archives - Montagnuolo, M.; Messina, A. (Journal of Digital Information Management, 2007)
Multimedia content classification and retrieval are indispensable tools in the current convergence of audiovisual entertainment and information media. Thanks to the development of broadband networks, every consumer will have digital video programmes available on-line as well as through the traditional distribution channels. In this scenario, since the early '90s, the most important TV broadcasters in Europe have started projects whose aim was to achieve preservation, restoration and automatic documentation of their audiovisual archives, In particular, the association of low-level multimedia features to knowledge and semantics for the purpose of automatic classification of multimedia archives is currently the target of many researchers in both academic and IT industrial communities, This paper describes our research direction, which is focusing on three points: (a) We first introduce a new taxonomy for classification of broadcast digital archives based on a novel theoretical approach. The advantage of this taxonomy is that it can provide an unambiguous representation of multi-media informative content from the relevant points of view to the broadcasters community. (b) We secondly present a multilayer multimedia database model to represent both structure and content of multimedia objects. (c) We further propose a framework architecture for building a Multimedia Fuzzy Annotation System (MFAS), and a description of our experimental plan.
Keywords: Knowledge-based multimedia systems; Semantic multimedia retrieval and annotation; Video taxonomy

Multi-objective mapping for NoC architectures - Benyamina, A. El H.; Boulet, P. (Journal of Digital Information Management, 2007)
In order to improve the performance of current embedded systems, Network -on-Chip (NoC) offers many advantages, especially in terms of flexibility and low cost. Applications require more and more intensive computations, especially multimedia applications such as video encoding. Developing product and application using such an architecture offers many challenges and opportunities. Many tools will be required to develop a NoC architecture for a specific application. A toot which can map and schedule an application or a set of applications to a given NoC architecture will be essential and must be able to satisfy many relative trade-offs (real-time, performance, low power consumption, time to market, re-usability, cost, area, etc). In this paper, we survey most approaches used to solve this problem with different goals. We then describe our approach based on a genetic algorithm and its implementation and its design objective.
Keywords: Genetic algorithms; Mapping objective; MPSoC; Network-on-chip; Optimization

Multi-source remote sensing classification based on Mallat fusion and residual error feature selection - Cao, D.; Yin, Q.; Guo, P. (Journal of Digital Information Management, 2007)
Classification of multi-source remote sensing images has been studied for decades, and many methods have been proposed or improved. Most of these studies focus on how to improve the classifiers in order to obtain higher classification accuracy. However, as we know, even if the most promising method such as neural network, its performance not only depends on the classifier itself, but also has relation with the training pattern (i.e. features). On consideration of this aspect, we propose an approach to feature selection and classification of multi-source remote sensing images based on Mallat fusion and residual error in this paper. Firstly, the fusion of multi-source images can provide a fused image which is more preferable for classification. And then a featureselection scheme approach based on fused image is proposed, which is to select effective subsets of features as inputs of a classifier by taking into account the residual error associated with each land-cover class. In addition, a classification technique base on selected features by using a feed-forward neural network is investigated. The results of computer experiments carried out on a multisource data set confirm the validity of the proposed approach.
Keywords: Feature selection; Mallet fusion; Multi-source classification; Neural network; Residual error

A method for incorporating user modelling - de Vrieze, P.; van Bommel, P.; van der Weide, T. (Journal of Digital Information Management, 2006)
In this paper a method is presented for adding user modelling to (existing) software systems. The method consists of seven steps that lead from initial analysis to the definition and evaluation of the elements needed for the adaptive behaviour. Along with the method, the central concepts of adaptation elements and adaptation graphs are introduced. An adaptation element can be used to determine the impact of personalisations, while adaptation graphs describe the adaptation in a system as a whole.
Keywords: Adaptation graphs; Adaptive hyper media; Software systems; User modeling techniques

A model for the aggregation of QoS in WS compositions involving redundant services - Jaeger, M.C.; Ladner, H. (Journal of Digital Information Management, 2006)
A composition arranges available services resulting in a defined flow of tasks. A discovery process identifies the suitable candidate services for a composition. A subsequent selection process chooses the optimal candidate for each task. The selection process can consider different quality-of-service (QoS) categories of the individual services to optimise the quality of the whole composition. The result is a quality-optimised assignment of candidates to each task. In this work, we discuss the case how already identified candidates, which a selection process originally has separated out, can improve a composition w.r.t. particular QoS categories. To realise this improvement, redundant arrangements involve the alternative candidates in order to supplement the originally assigned service. We formed these redundant arrangements on the basis of our previously introduced compositions patterns. The contribution of this work is a computational model that allows the aggregation of the QoS for the composition when these arrangements are applied. This work presents extensions and refinements to our previous work [jaeger etal 05] where the basic concepts of this computational model were already discussed.
Keywords: Quality aggregation; Software quality; Web service quality